2010
DOI: 10.7196/samj.3647
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous heparin levels in the controlled asthmatic patient

Abstract: Levels of circulating endogenous heparin in patients with diseases associated with inflammatory processes, such as asthma, are still unknown. Since heparin displays antiinflammatory properties, it is expected that the inhibitory effects on inflammatory mediators are reduced at low levels of endogenous heparin. 1 We present evidence supporting the hypothesis that asthmatic patients have lower levels of circulating endogenous heparin than healthy individuals have.Since 1955, endogenous plasma heparin has been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…130 Additionally, the same substrates increased hMSC osteogenic differentiation in a BMP signaling-dependent fashion in serum-containing osteogenic induction medium, again without supplemented GFs. 130 These studies suggested that endogenous circulating heparin, previously identified as a component of human blood plasma, 153,154 harnessed at engineered 2D interfaces could enrich and enhance the activity of endogenous GFs while foregoing the need for exogenous supplemented GFs.…”
Section: Engineered Approaches For Sequestering At 2d Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…130 Additionally, the same substrates increased hMSC osteogenic differentiation in a BMP signaling-dependent fashion in serum-containing osteogenic induction medium, again without supplemented GFs. 130 These studies suggested that endogenous circulating heparin, previously identified as a component of human blood plasma, 153,154 harnessed at engineered 2D interfaces could enrich and enhance the activity of endogenous GFs while foregoing the need for exogenous supplemented GFs.…”
Section: Engineered Approaches For Sequestering At 2d Interfacesmentioning
confidence: 99%
“…71 Further characterization will be required to determine whether GF sequestering with heparin-binding peptides (e.g. ATIII, PF4Zip, Hep-BP1-5, HEPpep) is a result of direct interactions with the GF or by indirect interactions with endogenous heparin or HS 153,154 in culture.…”
Section: Sequestering To and Controlled Release From 3d Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest therefore that patients with allergy, where there is regular mast cell degranulation in response to sensitising allergens, have been reported to have increased levels of "circulating heparin like material" (41) which may account for the observations that atopic patients can have a mild haemostatic defect (42), and even have evidence of less calcification of their arteries (43). However, more recent observations have suggested that there may a loss of heparin in the circulation of patients with asthma (44) and that some patients can have a hyper-coaguable state (45).…”
Section: Characterization Of Heparin Released From Mast Cellsmentioning
confidence: 99%
“…This group (Brunnee et al 1997;Nogi et al 1999) suggested that in allergic reactions mast cellderived heparin can act as a suitable surface to promote this cascade and can contribute to the generation of kinins to participate in the allergic response. However, a small clinical study compared plasma levels of endogenous heparin-like material between a group of patients with controlled asthma and healthy controls and found these levels to be reduced in the patient group; the authors conclude that the lack of heparin-associated anti-inflammatory activity in these individuals may be a significant factor in the disease (Davids et al, 2010).…”
Section: Pharmacology Of Heparin and Related Drugsmentioning
confidence: 99%